The acute effects of accentuated eccentric loading on drop jump kinetics in adolescent athletes - Lloyd, R. S.; Howard, S. W.; Pedley, J. S.; Read, P. J.; Gould, Z. I.; Oliver, J. L. (The Journal of Strength and Conditioning Research, 2022)
The purpose of the study was to determine the acute effects of accentuated eccentric loading (AEL) on drop jump kinetics in adolescent athletes. Fifteen male rugby players (mean ± SD: age = 16.2 ± 1.01, body mass = 73.38 ± 9.94, and height = 178.91 ± 6.74) completed 3 trials of a drop jump with and without an accentuated eccentric load using a dumbbell release technique that equated to 15% body mass. The addition of the AEL stimulus resulted in significant, moderate increases in jump height (p < 0.05; Wilcoxon r = 0.47) and braking and propulsive impulse (p < 0.05, Hedges' g = 0.43; p < 0.05, g = 0.61, respectively) but did not significantly influence reactive strength index. Concurrently, there were significant, moderate increases in ground contact times (p < 0.05; r = 0.45) and reductions in spring-like correlations (p < 0.05; g = 0.94). Neither the magnitude nor timing of peak landing force were significantly altered in the AEL protocol (p < 0.05, g = 0.38; p < 0.05, r = 0.10, respectively). Cumulatively, these data indicate that implementation of AEL resulted in meaningful improvements in jump height, driven by significant increases in braking and propulsive impulse. Despite extensions in ground contact times and reductions in spring-like behavior, neither peak landing force nor time to peak force were negatively altered by the AEL. These results indicate that adolescent athletes can realize superior vertical jump heights during drop jumps using AEL, without displaying marked changes in the magnitude or timing of peak landing force.